Eliciting individual preferences for pension reform - Yosr Abid Fourati; Cathal O'Donoghue (Center for Economic Studies and ifo Institute (CESifo), 2009)
Pension systems have recently been under scrutiny because of the expected population ageing threatening its sustainability. This paper's contribution to the debate is from a political economic perspective as it uses data from a Choice Experiment to investigate individual preferences for an alternative state pension scheme. Answers are used to estimate a life-cycle utility model of preferences towards pensions' parameters. Results suggest that individuals' value orientation is an important determinant of their preferences. Respondents' income determines which degree of redistribution is preferred. However, preferences according to age are in contradiction with what is suggested in theory.
Keywords: H0; I3; 330; population ageing; pension system reform; redistribution; stated preferences; Gesetzliche Rentenversicherung; Rentenreform; Einkommensumverteilung; Offenbarte Präferenzen; Alternde Bevölkerung; Lebenszyklus; Irland